PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DEWAN KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS LABA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dahlia, Eka Dila (Menara Ilmu, 2018)
This main aims of this study is to test whether the corporate governance mechanism which consistsof institutional ownership, managerial ownership, the proportion of independent board of directorsand audit committees affect the firm value, where the quality of earnings as an interveningvariable. The results of this study show that: (1) institutional ownership, managerial ownership,and audit committees does not affect the quality of earnings, (2) the proportion of independentboard of directors effect on the firm value, (3) the quality of earnings has no effect on the firmvalue, (4) of institutional ownership, managerial ownership, the proportion of independent boardof directors and audit committees does not affect on the firm value, (5) the quality of earnings isnot an intervening variable in relation to the mechanism corporate governance to firm value